Identification of Jasmonic Acid and Jasmonoyl-Isoleucine, and Characterization of AOS, AOC, OPR and JAR1 in the Model Lycophyte Selaginella moellendorffii. (13th March 2017) - Pratiwi, Putri; Tanaka, Genta; Takahashi, Tomohiro; Xie, Xiaonan; Yoneyama, Koichi; Matsuura, Hideyuki; Takahashi, Kosaku
Abstract : Jasmonic acid (JA) is involved in a variety of physiological responses in seed plants. However, the detection and role of JA in lycophytes, a group of seedless vascular plants, have remained elusive until recently. This study provides the first evidence of 12-oxo-phytodienoic acid (OPDA), JA and jasmonoyl-isoleucine (JA-Ile) in the model lycophyte Selaginella moellendorffii. Mechanical wounding stimulated the accumulation of OPDA, JA and JA-Ile. These data were corroborated by the detection of enzymatically active allene oxide synthase (AOS), allene oxide cyclase (AOC), 12-oxo-phytodienoic acid reductase 3 (OPR3) and JA-Ile synthase (JAR1) in S. moellendorffii. SmAOS2 is involved in the first committed step of JA biosynthesis. SmAOC1 is a crucial enzyme for generating the basic structure of jasmonates and is actively involved in the formation of OPDA. SmOPR5, a functionally active OPR3-like enzyme, is also vital for the reduction of (+)- cis -OPDA, the only isomer of the JA precursor. The conjugation of JA to Ile by SmJAR1 demonstrates that S. moellendorffii produces JA-Ile. Thus, the four active enzymes have characteristics similar to those in seed plants. Wounding and JA treatment induced the expression of SmAOC1 and SmOPR5. Furthermore, JA inhibited the growth of shoots in S. moellendorffii, which suggests that JA functions as a signaling molecule in S. moellendorffii. This study proposes that JA evolved as a plant hormone for stress adaptation, beginning with the emergence of vascular plants.